A Green Fuzzy Multi-Criteria Decision Making Model for Pharmaceutical Waste Disposal Management - Ahmad Mustaffa, Nurakmal; Zaibidi, Nerda Zura; Ahmad, Nazihah; Ang, Wei Chern (UUM, 2022)
Pharmaceutical waste known as hazardous substances should be disposed of in the best possible manner to avoid harm toward public health and the environment. Hence, designing a green decision-making model for pharmaceutical waste disposal management is needed at this point. To achieve the objective, this research intended to investigate the criteria, sub-criteria and disposal treatments that incorporate the green practice for disposing of pharmaceutical waste. This research also aimed to find the importance weights of criteria and sub-criteria, which later are adopted to rank the disposal treatments. In addition, the sensitivity analysis is also proposed to be conducted. By using a systematic literature review and experts’ opinions that involved the policymakers from the Ministry of Health Malaysia, a comprehensive list of criteria, sub-criteria and disposal treatments are successfully collected. To compute the importance weights and rank the disposal treatments for pharmaceutical waste, the data is collected from the respondents who are actively involved in the waste management fields, which include the Ministry Health of Malaysia, Kualiti Alam Sdn Bhd, Radicare (M) Sdn Bhd, Medivest Sdn Bhd and academician from Higher Education Institution. A set of questionnaires is used as a medium of data collection and Fuzzy Delphi TOPSIS (FDT) is employed to analyze data from the questionnaire. By considering the importance weights of economic, environmental, social and technical criteria, the results revealed that waste immobilization (encapsulation) is ranked as the best disposal treatment, which is followed by incineration, secured landfill and chemical disinfection. Next, the sensitivity analysis is conducted according to the eight scenarios to evaluate and check the influence of different importance weights toward the final model. Findings from the sensitivity analysis indicated that the final model is robust and can be implemented in Malaysia’s current pharmaceutical waste disposal management.